A review of the Munidopsidae Ortmann, 1898 (Decapoda, Galatheoidea) in Chilean waters, including new records for the Southeastern Pacific - Guzman, Guillermo L.; Sellanes, Javier (Zootaxa, 2015)
The information about the family Munidopsidae in Chile is scarce and sparse, making identification of new material. difficult. Due to this we lack precise information about the number and accurate distribution of Chilean species. Recent expeditions to Chile have collected specimens of this group, allowing an exhaustive review of the registers and collections in four museums in the country. A total of 93 specimens from six expeditions were analyzed, belonging to twelve species, of which five represent first records for the Chilean waters. The family in Chile is now composed by 19 bathyal and abyssal species; three belong to the genus Galacantha and 16 to Munidopsis. Only three species have distributions restricted to southeastern Pacific waters (M. cochlearis, M. follirostris and M. opalescens). Three other species are widely distributed along the eastern Pacific from Alaska or from Oregon to Chile (M. aspera, M. quadrata and M. verrucosus). No relationships were observed between the extensive geographical distribution of species and the bathymetric distribution.